HUBUNGAN ANTARA SELF AWARENESS DENGAN KEDISIPLINAN ANAK USIA 5-6 TAHUN DI TK RAUDHATUL ATHFAL IKHLAS KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Nurhayani, Nurhayani; Novianti, Ria; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The background of this study because of the low discipline in children. Self awareness has an important role in children’s discipline. A good self awareness will have a positive impact on the development of children's discipline. Without being supported by an nature,it will be difficult to reach children who have good dicipline. This study aimed to find out the relationship between self awareness and discipline in children aged 5-6 years old at Raudhatul Athfal Ikhlas Kindergarden School Subdistrict Payung Sekaki Pekanbaru City. This study was quantitative study with correlation study type. Sampling technique used in this study is a sample saturated with a total sample of 40 children. The data collection techniques were used observation sheets. The data analysis techniques were used Pearson Product Moment Correlation Coefficient. Based on the hypothesis test result obtained correlation coefficient value of rxy = 0.553, it is greater than rtable = 0.304 (0,553 > 0,304) with significance level of 0,000 < 0,05. Level relationship resides in the strong category with the resulting determinant coefficient value is of 30,6% it can be seen that the self awareness contribution of 30,6% to discipline.Keyword: Discipline, self awareness